2019
DOI: 10.1111/jth.14483
|View full text |Cite
|
Sign up to set email alerts
|

Could the YEARS algorithm be used to exclude pulmonary embolism during pregnancy? Data from the CT‐PE‐pregnancy study

Abstract: Introduction:The recently proposed YEARS algorithm was shown to safely exclude pulmonary embolism (PE) and reduce the use of computed tomography pulmonary angiography (CTPA) among pregnant women with suspected PE. Our aim was to externally validate this finding. Methods:We performed a post hoc analysis of a prospective management outcome study for PE diagnosis in pregnant women. PE was diagnosed with an algorithm that combined the revised Geneva score, D-dimer testing, bilateral lower-limb compression ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 18 publications
1
37
1
Order By: Relevance
“…Using this approach, 39% of women were able to avoid diagnostic imaging, with an acceptably low three month venous thromboembolism incidence of 0.21% (0.04% to 1.2%). Furthermore, post hoc retrospective application of this pregnancy adapted YEARS algorithm to the cohort of patients in the first study showed similar findings, with 21% of women meeting criteria for exclusion of pulmonary embolism without diagnostic imaging and no venous thromboembolism events during follow-up 52. Limitations of these studies include relative small sample sizes and possible bias for inclusion of patients at lower risk.…”
Section: Diagnosismentioning
confidence: 62%
“…Using this approach, 39% of women were able to avoid diagnostic imaging, with an acceptably low three month venous thromboembolism incidence of 0.21% (0.04% to 1.2%). Furthermore, post hoc retrospective application of this pregnancy adapted YEARS algorithm to the cohort of patients in the first study showed similar findings, with 21% of women meeting criteria for exclusion of pulmonary embolism without diagnostic imaging and no venous thromboembolism events during follow-up 52. Limitations of these studies include relative small sample sizes and possible bias for inclusion of patients at lower risk.…”
Section: Diagnosismentioning
confidence: 62%
“…None of these women had PE diagnosed during the initial workup or 3-month follow-up, for a failure rate of the pregnancy-adapted YEARS algorithm of 0% (95% CI, 0.0-3.9%). 73 At present, the pregnancy-adapted YEARS algorithm is the best validated method for diagnosing and excluding PE in pregnancy.…”
Section: No Datamentioning
confidence: 99%
“…A post hoc analysis of the previously mentioned Swiss-French prospective management study 31 assessed the accuracy and safety of the pregnancyadapted YEARS algorithm in women with suspected PE. 12 Also in this analysis, the algorithm proved to be well tolerated with no VTE occurring during follow up (0%, 95% CI 0-3.9).…”
Section: Diagnostic Management Of Vte In Pregnant Patientsmentioning
confidence: 99%